Does the Introduction of Futures on Emerging Market Currencies Destabilize the Underlying Currencies? - Jochum, Christian (IMF Working Papers; Working Paper ;, 1998)
Recent interest in futures contracts on emerging market currencies has raised concerns among some central bank authorities about their ability to maintain stable currencies. This paper presents empirical results examining the influence of the Mexican peso, the Brazilian real, and the Hungarian forint futures contracts on the respective spot markets. While measures of linear dependence and feedback indicate strong connections between the respective markets, futures volatility does not significantly explain spot market volatility, nor does it increase after futures introductions. To account for the characteristics of the spot and futures returns a SWARCH model has been employed to estimate volatility.